1996
DOI: 10.1111/j.1467-8578.1996.tb00951.x
|View full text |Cite
|
Sign up to set email alerts
|

Professional development to meet special educational needs

Abstract: March this year saw the publication of the first report for more than ten years to address key issues concerning the initial training, induction and continuing professional development of teachers with responsibilities for pupils with special educational needs. Entitled Professional Development to Meet Special Educational Needs the Report has been produced by a working party of the Special Educational Needs Training Consortium (SENTC) and funded by the Department for Education and Employment. Olga Miller, Chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A Department for Education and Employment (DfEE) survey in 1995 found that almost 46% of teachers in schools for children with severe learning difficulties (SLDs) had no specialist training (Miller & Garner 1996). A range of accredited Continuing Professional Development (CPD) courses and modules exist in ASD in the UK, as publicized in the Good Autism Practice Journal published by the British Institute of Learning Disabilities.…”
Section: The Need For the Guidancementioning
confidence: 99%
“…A Department for Education and Employment (DfEE) survey in 1995 found that almost 46% of teachers in schools for children with severe learning difficulties (SLDs) had no specialist training (Miller & Garner 1996). A range of accredited Continuing Professional Development (CPD) courses and modules exist in ASD in the UK, as publicized in the Good Autism Practice Journal published by the British Institute of Learning Disabilities.…”
Section: The Need For the Guidancementioning
confidence: 99%